Smart Cities, Green Technologies, and Intelligent Transport Systems 4th International Conference, SMARTGREENS 2015, and 1st International Conference VEHITS 2015, Lisbon, Portugal, May 20-22, 2015, Revised Selected Papers - Helfert, Markus; Krempels, Karl-Heinz; Klein, Cornel; Donellan, Brian; Guiskhin, Oleg (Communications in Computer and Information Science, 2015)
This book constitutes the thoroughly refereed proceedings of the 4th International Conference on Smart Cities and Green ICT Systems, SMARTGREENS 2015, and the 1st International Conference on Vehicle Technology and Intelligent Transport Systems, VEHITS 2015, held in Lisbon, Portugal, in May 2015. The 15 full papers of SMARTGREENS 2015 presented were carefully reviewed and selected from 73 submissions. VEHITS 2015 received 27 paper submissions from which 3 papers were selected and published in this book. The papers reflect topics such as smart cities, energy-aware systems and technologies, sustainable computing and communications, sustainable transportation and smart mobility.